Implementación del sistema de gestión de seguridad y salud en el trabajo de acuerdo a lo establecido por el Instituto Ecuatoriano de Seguridad Social en la Empresa AIG Metropolitana - Cárdenas Pareja, Alex Daniel (2016)
The objective of this project was the development of a systematization of the experience obtained of the Implementation of the Security and Occupational Health Management System of AIG Metropolitan Company, through the analysis of the most significant events that occurred during the activities of the implementation. The system is based on the legal regulations of the Ecuadorian State through its representative bodies in the field, as the Ecuadorian Institute of Social Security and the Labor Relations Ministry along with some international regulations applicable to the reality of the company Starting from an initial diagnosis of the current situation of the company incompliance with the applicable local laws, along with situational analysis of the organization and its members, we developed the action plan which was successfully implemented From this time we could recognize several successes and problems, among the most important ones were the relationship between the state of health of employees and sub-standard conditions they were exposed because of omissions of the company and the modification of these resulted in decreasing the frequency and severity of organizational morbidities This document seeks to provide tools for a successful implementation of a Security and Occupational Health Management System, at the same time this project facilitates the understanding of all the variables that one of these processes generate in the individualities of the members of the organization.